Strength and sorption properties of some selected paper-cement boards in Ibadan metropolis (2012)
Paper Cement Board (PCB) were obtained from four selected small scale manufactures in Ibadan, Oyo state, Nigeria. Data on the production process, materials used for production and paper-cement ratio in the mix were also collected from source. Strength and sorption properties were carried out on the boards. The properties of PCBs were compared with those of the commonly used fibre and gypsum board. One out of the four industries engaged in semi-mechanised production. Analysis of variance showed that boards made from mechanised process were significantly different from the other boards, but the different between the other PCBs was not significant (p<0.05). The results revealed that boards produced by mechanised process exhibited higher Modulus of Rapture (MOR) and Modulus of Elasticity (MOE) of 3.06N/mm2 and 2140.13N/mm2 respectively and 45.3% water absorption (WA) after 24h immersion. A comparison of the PCBs with gypsum and fibreboards did not prove the PCBs inferior in any of the properties evaluated. All the tested samples had low strength properties and high WA and are hence not suitable for structural purposes and exterior applications